صعوبة اكتساب مهارة التحدث لدى تلاميذ السنة الخامسة ابتدائي - بوعودة, حفصة (كلية الأدب العربي والفنون, 2024)
يعد التحدث المهارة الأهم في التواصل اللغوي، نظرا لكونه الأيسر استخداما والأكثر ممارسة في العملية التواصلية، فالاستماع رغم كثرة الاعتماد عليه في التواصل وأهميته في عملية التعلم والتعليم بوجه عام والبناء اللغوي للمتعلم على وجه الخصوص، فإن التحدث تزداد أهميته كونه محصلة الكثير من مهارات اللغة ووعاء للبناء الفكري، فبدونه يصعب على المتعلم استدراك ما سبقه والتعبير عن نفسه، وهو الذي يعكس القدرة على امتلاك ناصية اللغة والتعبير عن النفس لإشباع الحاجات وتنفيذ المتطلبات، فضلا على أنه يبرز شخصية المتعلم ومستوى ثقافته، ويعكس مستوى الفهم والوضوح لديه إذا تحدث Speakingis the most important skill in linguistic communication, giventhatitis the easiest to use and the mostpracticed in the communicative process.Listening, despite the heavyreliance on it in communication and its importance in the learning and teachingprocess in general and the learner’slinguistic construction in particular, speakingbecomesincreasingly important as itis the result of manylanguageskills and a vessel. For intellectual structure, withoutititisdifficult for the learner to comprehendwhat came before and express himself, whichreflects the ability to possess the language and express oneself to satisfyneeds and implementrequirements. In addition, ithighlights the learner’spersonality and level of culture, and reflectshislevel of understanding and claritywhenhespeaks
Keywords: اللغة العربية، مهارة التحدث، العملية التعليمية.; Arabiclanguage, speakingskill, educationalprocess.